Students' Perceptions on Memorylingo to Improve Their Listening Skill - Yunus, Aulia; Salmiah, Maryati (Institut Agama Islam Negeri Palopo, 2025)
This study investigates students’ perceptions of using the MemoryLingo application to enhance their English listening skills. Employing a qualitative case study approach, the research involved 34 junior high school students who completed questionnaires, with two purposively selected participants interviewed to gain deeper insights. Data were collected through Likert-scale questionnaires and semi-structured interviews, focusing on comprehension, engagement, confidence, and independent learning. The results indicate that the majority of students (over 85%) agreed or strongly agreed that MemoryLingo improved their listening comprehension, accuracy, and ability to identify key spoken phrases. Participants reported that features such as interactive exercises, audio-visual content, and immediate feedback were highly effective in facilitating learning. Thematic analysis revealed four central themes: improved comprehension, increased confidence, promotion of independent practice, and the benefits of interactive features. Although some students noted difficulties in processing fast-paced audio, overall perceptions were positive. The findings suggest that MemoryLingo can serve as a valuable supplementary tool in listening instruction, supporting both classroom learning and autonomous study. This study highlights the practical relevance of integrating digital tools into English language education and recommends further research with larger and more diverse samples to explore long-term impacts and comparative effectiveness with other learning applications. Future research should examine its long-term effects and compare its impact with other digital tools.